Evaluation and optimization of heat extraction device - Azri Amzari, Ramli (2010)
This report is an outcome of the final year project entitled Evaluation and Optimization of Heat Extraction Device. The project contains two objectives, first to optimize the heat extraction device in the means of design, way of fabrication and to figure out where is the suitable placement for the fabricated device inside Proton Waja car. Second, the project require researcher to gather as much information available by experimenting on the device in two manipulated condition, heat increment inside Waja car compartment with and without the existent of the heat extraction device. The device is handmade by using a flexible duct and CPU fan to extract heat from the car the environment. Four experiments were done, experiment 1 and 2 is for without the heat extraction device and experiment 3 and 4 with heat extraction device. The device is controlled by heat management system that will acts as a switch to automatically turn the blower on at 40oC. The highest temperature data taken from each experiment are 78.0oC, 75.4oC, 61.3oC and 61.5oC respectively for experiment 1, 2, 3 and 4. The result shows that the existence of heat extraction device can reduce the heat built up inside the car cabin.